pH sensitive hydrogel based on poly(acrylic acid) and cellulose nanocrystals - Lim, Sze Lim; Ishak Ahmad,; Azwan Mat Lazim, (Universiti Kebangsaan Malaysia, 2015)
The purpose of this study was to produce a novel pH sensitive hydrogel with superior thermal stability, composed of poly(acrylic acid) (PAA) and cellulose nanocrystal (CNC). CNC was extracted from kenaf fiber through a series of alkali and bleaching treatments followed by acid hydrolysis. PAA was then subjected to chemical cross-linking using the cross-linking agent (N,N-methylenebisacrylamide) in CNC suspension. The mixture was casted onto petri dish to obtain disc shape hydrogel. PAA/cellulose hydrogel with the same composition ratio were also prepared as control. The effect of reaction conditions such as the ratio of PAA and CNC on the swelling behavior of the hydrogel obtained towards pH was studied. The obtained hydrogel was further subjected to different tests such as thermogravimetric analysis (TGA) to study the thermal behavior, Fourier transform infrared for functional group identification and swelling test for swelling behavior at different pH. The cross-linking of PAA was verified with FTIR with the absence of C=C double bond. In TGA test, PAA/CNC hydrogel showed significantly higher thermal stability compared with pure PAA hydrogel. The hydrogel obtained showed excellent pH sensitivity and experienced maximum swelling at pH7. The PAA/CNC hydrogel can be developed further as drug carrier.